1988
DOI: 10.1017/s0033822200043915
|View full text |Cite
|
Sign up to set email alerts
|

The Relations Between Carbon Isotope Composition and Apparent Age of Freshwater Tufaceous Sediments

Abstract: ABSTRACT. This paper presents a synthetic approach to 14C dating of calcareous tufa, based on statistical analysis of correlations betwen lithologic type of tufaceous sediment, carbon isotope composition, and apparent age. Experimental data on several profiles from southern Poland and the United Kingdom reveal either constant or systematically changing values of apparent age. Constant value of apparent age in a profile can be attributed to calcareous muds precipitated from stagnant or low-energy water, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
4
21
0
1
Order By: Relevance
“…3) and 76.1 pMC for Lake Kozjak. Constant b13C and b180 values throughout the profiles (Srdoc et al 1986b) indicate stable environmental conditions during the sedimentation period and hence, the constant Ao value (Pazdur 1988). …”
Section: Dating the Organic Component Of Sedimentmentioning
confidence: 98%
See 1 more Smart Citation
“…3) and 76.1 pMC for Lake Kozjak. Constant b13C and b180 values throughout the profiles (Srdoc et al 1986b) indicate stable environmental conditions during the sedimentation period and hence, the constant Ao value (Pazdur 1988). …”
Section: Dating the Organic Component Of Sedimentmentioning
confidence: 98%
“…In an early study of groundwater dating, Geyh (1973) ranged values according to the geology of the catchment area. Other studies of the initial activity of calcareous deposits (Thorpe, Otlet & Sweeting 1980;Srdoc et al 1983Srdoc et al ,1986aPazdur 1988;Pazdur, Pazdur & Szulc 1988; Horvatincic et al 1989;Pentecost et al 1990) showed that the Ao depends on geological setting, geochemical processes, vegetation and climate, which are, in principle, site-specific. A temporal change of Ao is not very likely over a period of stable environmental conditions, as demonstrated by our data for Holocene samples.…”
Section: Introductionmentioning
confidence: 99%
“…(11 samples) and Lublin Upland (63 samples). Tufas were deposited in the stream channels, and also within cupola spring mires characteristic for part of the Lublin Upland (Dobrowolski et al, 1999;Pazdur 1988;Pazdur et al, 2002a and2002b). CaCO 3 precipitated in conditions of relatively higher temperature.…”
Section: Calcareous Tufasmentioning
confidence: 99%
“…In earlier studies of tufa profiles from southern Poland (Pazdur, Pazdur & Szulc 1988;Pazdur 1988) we found highly different values of the reservoir correction factor TR of the carbonate fraction of tufa samples, ranging from 900-11,000 yr. Observed values of TR are related to the lithologic type of tufa.…”
Section: Introductionmentioning
confidence: 68%